Extractive Spectrophotometric Determination of Ondansetron Hydrochloride in Pure and Dosage Forms by Using Alizarin Red-S and Bromothymol Blue - Ramu, G.; Biksham Babu, A.; Venkata Rao, S.; Rambabu, C. (Asian Journal of Chemistry, 2011)
Two simple, sensitive and accurate visible spectrophotometric methods have been developed for quantification of odansetron in pure and dosage formulations. These methods (method A & B) are based on the extraction of ion-ion associated complex between ondansetron HCl and acidic dyes such as alizarin red-S (ARS) and bromothymol blue (BTB) into chloroform solvent. The coloured products thus formed showed maximum absorbance at 425 and 420 nm for alizarin red-S and bromothymol blue respectively. Beer's law plots are linear over the range of concentrations 3.3-20.0 and 8.3-50.0 μg/mL with correlation coefficients 0.9997 and 0.9999 for the two methods A and B respectively. Different parameters which are affecting the reaction pathway are studied and optimized. The results thus obtained are in good agreement with those of reference methods. The proposed methods are successfully applied for the determination of ondansetron hydrochloride either in pure or dosage formulations.